Trade and Innovation in MENA - Ficarra, Matteo; Gökten, Meryem; Harasztosi, Péter; Koczán, Zsóka; Lesma, Roberta; Pál, Rozália; Weiss, Christoph (World Bank, Washington, DC, 2022)
This paper examines trade participation and innovation activities and how they are intertwined in the Middle East and North Africa region. While the level of trade participation of firms in the region is similar to other peer economies, innovation rates are particularly low. Many productive firms, especially smaller firms, might not be able to reap the scale and efficiency benefits from trade and innovation activity because of the weak business environment in the region. The paper shows that innovative firms tend to be more productive when they trade, while exporters tend to grow faster (in terms of sales) when they also invest in innovation. In addition, the use of foreign-licensed technology appears to have a key role in innovation, even after controlling for the effects of trade participation and foreign ownership. The paper also finds that traders and innovative firms were more likely to adapt to the COVID-19 crisis and the associated sharp sales shock. Overall, the results confirm the importance of international technology diffusion in the innovation process through access to foreign markets.